2019
DOI: 10.3390/su11092654
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Addressed by Swedish Third-Party Logistics Providers Conducting Sustainable Logistics Business Cases

Abstract: The sustainable logistics business case (SLBC) provides underlying argumentation to convince decision makers to approve initiatives within sustainable logistics. Little knowledge exists on how companies conduct SLBCs or the challenges that need to be addressed. The purpose of this paper is to explore how companies conduct SLBCs, to increase the understanding of how perceived challenges can be addressed. Potential challenges were identified in literature on business cases models in general and sustainable logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 31 publications
(105 reference statements)
0
11
0
Order By: Relevance
“…Their commitment is characterised by, for example, capital expenditures, organisational changes and modified operating practices (Lieb and Lieb, 2010). Recent studies showed that some LSPs are becoming self-driven in their green engagement even with the lack of shippers' demands (Björklund and Forslund, 2019; Jazairy and von Haartman, 2020). However, no matter how proactive LSPs might be in their green engagement, they are eventually bound to follow what shippers request from them, and they adjust their operational procedures to satisfy shippers' needs (Lun et al , 2015; Sallnäs, 2016; Wolf and Seuring, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their commitment is characterised by, for example, capital expenditures, organisational changes and modified operating practices (Lieb and Lieb, 2010). Recent studies showed that some LSPs are becoming self-driven in their green engagement even with the lack of shippers' demands (Björklund and Forslund, 2019; Jazairy and von Haartman, 2020). However, no matter how proactive LSPs might be in their green engagement, they are eventually bound to follow what shippers request from them, and they adjust their operational procedures to satisfy shippers' needs (Lun et al , 2015; Sallnäs, 2016; Wolf and Seuring, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Its assumptions can thus help practitioners improve their BC approaches. According to Björklund and Forslund (2019), the most important challenges of making a proper BC are: the inclusion of a wide range of indicators, the ability to measure, quantify and integrate different dimensions, and to include trade-offs, influence from stakeholders, a time perspective and contextual considerations. The identified theories seem applicable to shed more light on how all of these challenges should be managed in practice.…”
Section: Discussionmentioning
confidence: 99%
“…A selective literature review II, similarly to literature review I, was performed with the aim to identify several criteria to act as building blocks for the TONF development rather than provide an exhaustive list of the criteria. The criteria were extracted from the literature from the field of eco-design [27,37] and sustainable supply chain management [38,39] identified in literature review I, as well as normative works on sustainability assessment [26,40]. The review focused on the proposals for dealing with sustainabilityrelated trade-offs during early integration of sustainability into business processes.…”
Section: Methodsmentioning
confidence: 99%